L-DOPA Treatment Selectively Restores Spine Density in Dopamine Receptor D2–Expressing Projection Neurons in Dyskinetic Mice - Suárez, Luz M.; Solís, Óscar; Caramés-Tejedor, José María; Taravini, Irene R.; Solís, José M.; Muller, Mario G.; Moratalla, Rosario (Elsevier, 2014)
L-3,4-dihydroxyphenylalanine (L-DOPA)–induced dyskinesia is an incapacitating complication of L-DOPA therapy that affects most patients with Parkinson’s disease. Previous work indicating that molecular sensitization to dopamine receptor D1 (D1R) stimulation is involved in dyskinesias prompted us to perform electrophysiological recordings of striatal projection “medium spiny neurons” (MSN). Wild-type and bacterial artificial chromosome transgenic mice (D1R and D2R) mice were lesioned with 6-hydroxydopamine and then treated with L-DOPA. Functional, molecular, and structural changes were assessed in corticostriatal slices. Individual MSNs injected with Lucifer-Yellow were detected by immunohistochemistry for three-dimensional reconstructions. Both D1R-MSNs and D2R-MSNs showed diminished spine density in totally denervated striatal regions in parkinsonian mice. Chronic L-DOPA treatment, which induced dyskinesia and aberrant FosB expression, restored spine density in D2R-MSNs but not in D1R- MSNs. In basal conditions, MSNs are more excitable in parkinsonian than in sham mice, and excitability decreases toward normal values after L-DOPA treatment. Despite this normalization of basal excitability, in dyskinetic mice, the selective D1R agonist SKF38393 increased the number of evoked action potentials in MSNs, compared with sham animals. Conclusions: Chronic L-DOPA induces abnormal spine re-growth exclusively in D2R-MSNs and robust supersensitization to D1R- activated excitability in denervated striatal MSNs. These changes might constitute the anatomical and electrophysiological substrates of dyskinesia.
Keywords: Parkinson, Enfermedad de; Three-dimensional neuronal reconstruction; Striatum; Parkinson’s disease; Medium spiny neuron; L-DOPA; Dyskinesia; Behavioral sensitization